Investigation of the plane wave coupling to a linearly loaded transmission line network - L. M. Galeev (Известия высших учебных заведений: Проблемы энергетики)
The article is concerned with a complex investigation of the influence of the plane wave coupling with a certain function of time, incident direction and polarization to a linearly loaded transmission line network comprised of three single-wire conductors with different lengths connected in the center. Line load is represented as 50 Ω resistors connected to all terminations of the transmission line network. The exemplary network was modeled on a computer and experimentally investigated in a gigahertz transverse electromagnetic GTEM cell, which allows creating an electromagnetic field of a certain direction. The coupled voltage at the terminals of the network was investigated in the frequency and time domains. To conduct an experiment in the frequency domain, both to create an electromagnetic field inside the GTEM camera and to measure the induced voltage at the terminations of the network, a vector network analyzer VNA was used. To conduct an experiment in the time domain for the sake of creating an electromagnetic field, a high-voltage voltage generator was used, whereas a strobing oscilloscope was used to measure the induced voltages. The simulation was performed in the LTspice software - a tool for calculating electrical and electronic circuits, and Matlab. It is also examined to show the compliance with the experimental results. On the basis of obtained results, the author was able to identify the main aspects that may be useful in modeling and predicting the electromagnetic processes occurring in linearly loaded conductors, power supply and / or data transmission systems.